Hyperleukocytosis in a neuroblastoma patient after treatment with natural killer T cells expressing a GD2-specific chimeric antigen receptor and IL-15 - Xin Xu; Shantan Reddy; Saleh Bhar; Frederic D Bushman; Amy N Courtney; Gabriel A Barragán; Gengwen Tian; Erica J Di Pierro; Leonid S Metelitsa; Antonino Montalbano; Hangjin Yu; Claudia Martinez Amador; et al. (Journal for ImmunoTherapy of Cancer)
The ability of immune cells to expand numerically after infusion distinguishes adoptive immunotherapies from traditional drugs, providing unique therapeutic advantages as well as the potential for unmanageable toxicities. Here, we describe a case of lethal hyperleukocytosis in a patient with neuroblastoma treated on phase 1 clinical trial (NCT03294954) with autologous natural killer T cells (NKTs) expressing a GD2-specific chimeric antigen receptor and cytokine interleukin 15 (GD2-CAR.15). This patient was the first to be treated on dose level (DL) 5 and the first patient whose product was restimulated with K562-derived artificial antigen-presenting cells (aAPCs) instead of autologous peripheral blood mononuclear cells (PBMCs). 12 previously treated patients on DLs 1 through 4 did not experience significant toxicity. Our root-cause analysis revealed no genetic alterations of known clinical significance and excluded the possibility of clonal expansion due to insertional retroviral mutagenesis. We report that the use of aAPCs instead of PBMCs for CAR-NKT restimulation contributed to a hyperproliferative state associated with distinct gene expression that possibly led to explosive lymphocyte expansion and uncontrolled toxicity in the patient. These findings warrant the implementation of measures to control immune cell activation during manufacture of cell therapy products, especially those armed with transgenic cytokines.